PERLINDUNGAN HUKUM TERHADAP PESERTA BPJS DALAM PERJANJIAN KERJASAMA ANTARA BPJS KESEHATAN CABANG UTAMA PURWOKERTO DENGAN RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Indira Swasti Gama Bhakti (Jurnal Idea Hukum, 2016)
The construction of the legal relationship between participants BPJS with BPJS Health is a social insurance; Health BPJS with Hospital Prof. Dr. Margono Soekarjo is an agreement to perform certain services pursuant to Article 1601 of the Civil Code; where responsibility for reimbursement by INA CBGs by BPJS to RSMS. The method used is the juridical approach to normative or legal research only examined the references so that it referred to legal research library. As for another approach used is the Analytical approach (Analytical Approach).Â Legal protection of participants BPJS in Hospital Prof. Dr. Margono Soekarjo, namely protection is based on two legal protection of participants BPJS by Social Security Law, the Law on Health Insurance BPJS and regulation as well as the Medical Practice Law, Health Law, and the Law Hospital. The pattern of legal protection by Social Security Law, the Law on Health Insurance BPJS and regulation is carried out through participant BPJS rights protection and the right to file a complaint related to health care in the National Health Insurance (JKN). While based on the Medical Practice Law, Health Law, and the Law Hospital, legal protection BPJS participants in Hospital Prof. Dr. Margono Soekarjo in the receiving health care in Hospital Prof. Dr. Margono Soekarjo.Keywords: BPJS, Legal Protection, Legal Relationship.Â